Learner autonomy in skill-based language improvement courses in an undergraduate ELT program - Baghbankarimi, Minou (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
The present study aimed to explore the extent to which the three skill-based language improvement courses in the first semester of the undergraduate English Language Teaching (ELT) program at Eastern Mediterranean University (EMU) promote learner autonomy as perceived by the students and the course instructors. To achieve this aim, the students‟ perceptions of learner autonomy in these courses were identified by administering them a questionnaire and the instructors‟ perceptions were obtained through interviews. Moreover, class observations were conducted to find out whether or not learner autonomy was actually promoted in the above mentioned classes. This study was a qualitative case study which includes both qualitative and quantitative data. It was also an evaluation study which adopted naturalistic and descriptive inquiry approach. The participants of the study were 87 students taking the three skill-based courses and the four instructors teaching these courses. Both qualitative and quantitative data were gathered through three parallel student questionnaires, teacher interviews, and class observations. The results of the study revealed that generally the three skill-based language improvement courses promote learner autonomy, as perceived by the students. However, the instructors‟ perceptions of learner autonomy in these courses were comparatively less positive. In other words, the teachers stated that they try to promote learner autonomy in their classes through some activities such as strategy training, and giving options in presentation or project topics, but due to some reasons like students‟ backgrounds, course materials, etc., they cannot fully foster learner autonomy in these courses. Similarly, the class observations also show that only few class activities were leading to learner autonomy. In addition, the results of the study included some suggestions from the students and the instructors; they proposed to make some changes in the existing courses in order to make them more effective in terms of promoting learner autonomy. To conclude, the findings of the present study may have the following implications for teaching and further research: i) The existing materials should be replaced by the materials which include more strategy-training and more activities/tasks promoting autonomy; ii) Various supplementary/self-study activities should be utilized; and, iii) The students should be involved in decision making. Keywords: Autonomy, Leaner Autonomy, Decision Making, Strategy Training, Perceptions.

ÖZ: Bu araştırma, Doğu Akdeniz Üniversitesi (DAÜ) İngiliz Dili Eğitimi Bölümü (ELT) lisans programının ilk döneminde yer alan üç beceri tabanlı dil geliştirme derslerinin, özerk öğrenmeyi ne derece desteklediğinin öğrenciler ve öğretmenler tarafından nasıl algılandığını araştırmayı hedeflemektedir. Bu amaca ulaşmak için öncelikle, özerk öğrenmenin öğrenciler tarafından nasıl algılandığı, onlara uygulanan bir anket ile tespit edilmiştir. İkinci olarak, öğretmenlerin algıları görüşme yoluyla elde edilmiştir. Aynı zamanda, sınıf gözlemleriyle özerk öğrenmenin aslında olup olmadığına da bakılmıştır. Bu nitel durum çalışması, beceri tabanlı dil geliştirme derslerini alan 87 öğrenci ve bu dersleri veren 4 öğretmenden oluşan örneklemle, betimlemeli yöntem içeren değerlendirme çalışmasıdır. Nicel ve nitel veriler öğrenci anketleri, öğretmen görüşmeleri ve sınıf gözlemleri ile toplanmıştır. Çalışmanın sonuçları, genel olarak öğrencilerin algıları üç beceri tabanlı dil geliştirme derslerinin, bağımsız öğrenmeyi teşvik ettiği yönündedir. Ancak, öğretmenlerin algısı öğrencilere göre nispeten daha az olumludur. Diğer bir deyişle, öğretmenler, bazı etkinliklerle özerk öğrenmeyi desteklerken, öğrencilerin özgeçmişleri veya ders materyalleri gibi nedenlerden dolayı özerk öğrenmeyi tam olarak teşvik edemediklerini vurgulamışlardır. Benzer sonuçlar sınıf gözlemlerinde de ortaya çıkmıştır; ancak birkaç sınıf etkinliğinin özerk öğrenmeyi desteklediği görülmüştür. Buna ek olarak, çalışmanın sonuçları bazı öğrenci ve öğretmenlere ilişkin önerileri kapsamaktadır. Yapılan öneriler, derslerde bazı değişikliklere gidilerek özerk öğrenmenin daha etkin bir şekilde teşvik edilmesi yönündedir. Sonuç olarak, bu çalışmanın bulguları bazı işlevsel ve kuramsal sezdirimleri ortaya koymaktadır : i) Mevcut ders materyalleri daha çok strateji eğitimi ve özerkliği arttıracak etkinlikleri içeren yenileriyle değiştirilmelidir; ii) Çeşitli ek/kendi kendine çalışma faaliyetleri kullanılmalıdır; iii) öğrenciler karar verme sürecine dahil edilmelidirler. Anahtar Kelimeler : Özerklik, Özerk Öğrenme, Karar Verme, Strateji Eğitimi, Algılar
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2014. Supervisor: Assist. Prof. Dr. Fatoş Erozan.
Keywords: English Language Teaching; English Language - Study and Teaching - Eastern Mediterranean University; Language Learning - Autonomy; Language and languages - Study and teaching - Learner autonomy - Second language acquisition; Autonomy; Learner Autonomy; Decision Making; Strategy Training; Perceptions